Objective: Antifungal activity of total ethanolic extract and fractions of Usnea varieties were proved against Aspergillus niger, Penicillium digitatum, and Rhizopus nigricans fungi. Methods: To perform the study of relative antifungal activity (AFR), flu - GACHA, DAYANNA CABRA; OSPINA, LUIS POMBO; PALACIOS, JANETH ARIAS; AGUIRRE, OSCAR RODRÍGUEZ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Antifungal activity of total ethanolic extract and fractions of Usnea varieties were proved against Aspergillus niger, Penicillium digitatum, and Rhizopus nigricans fungi. Methods: To perform the study of relative antifungal activity (AFR), fluconazole and ketoconazole were used as standards. The inhibition coefficient 50 (IC50) for each extract and the fractions was determined. Results: It was established that the highest activity was presented by the acetone fraction with a value of 58.53. In the study of antifungal activity, the fraction that presented the best activity against P. digitatum was ethanolic with a value of 44.33, while for R. nigricans was petrol extract, with a value of 75.35 and finally for A. niger was the total extract with a value of 35.48. Conclusions: Comparing the values obtained from the extract and the different fractions resulted in the dichloromethane fraction showing the best values.